2003
DOI: 10.4319/lo.2003.48.1_part_2.0337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optically shallow bottoms on upwelling radiances: Bidirectional reflectance distribution function effects

Abstract: Radiative transfer simulations were carried out for a variety of measured and modeled benthic bidirectional reflectance distribution functions (BRDFs), incident lighting conditions, bottom depths, and water inherent optical properties. These simulations quantify the errors that occur in predictions of above-surface remote-sensing reflectances and in-water upwelling radiances if non-Lambertian ocean bottoms are replaced by Lambertian bottoms having the same irradiance reflectance. We found that when computing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 18 publications
(20 reference statements)
1
59
0
1
Order By: Relevance
“…Although the simulations included the usual assumption of Lambertian ocean floor reflectance and comparisons with field measurements were not considered, the work indicated that the resulting simulations were at least consistent between models using a variety of numerical approaches to solve the radiance-based problem. A comprehensive text on the general subject of oceanic radiative transfer was published the following year (Mobley 1994). In that same year, the first instance of an ocean radiative transfer model validation effort was reported-a simple one-dimensional irradiance model was compared with field measurements (Maritorena et al 1994).…”
Section: Historical Investigationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the simulations included the usual assumption of Lambertian ocean floor reflectance and comparisons with field measurements were not considered, the work indicated that the resulting simulations were at least consistent between models using a variety of numerical approaches to solve the radiance-based problem. A comprehensive text on the general subject of oceanic radiative transfer was published the following year (Mobley 1994). In that same year, the first instance of an ocean radiative transfer model validation effort was reported-a simple one-dimensional irradiance model was compared with field measurements (Maritorena et al 1994).…”
Section: Historical Investigationsmentioning
confidence: 99%
“…An approach to replacing the constant reflectance factor with a morphologybased parameterization of a seagrass canopy was reported by Ackleson and Klemas (1986) using a one-dimensional analytical approach to solving the irradiance-based transfer problem; however, as in the previous work, the means to validate the model in the field were not available. Mobley et al (1993) reported an intermodel comparison representing a comprehensive set of environmental scenarios that included the effects of an optically shallow water column. Although the simulations included the usual assumption of Lambertian ocean floor reflectance and comparisons with field measurements were not considered, the work indicated that the resulting simulations were at least consistent between models using a variety of numerical approaches to solve the radiance-based problem.…”
Section: Historical Investigationsmentioning
confidence: 99%
See 3 more Smart Citations